The result of "Gastrovit" preparation influence on bioelectrical activity of rat's stomach - Lkhamsaizmaa, D; Byambajav, Ts (Mongolian Journal of Agricultural Sciences, 2014)
We determined purposely the "Gastrovit" preparation influence results from Badaan (Bergena crassifolia L.) and Seabuckthorn (Hippophae rhamnoides L) in the bioelectrical activity of rat’s stomach during acetic acid ulcer models of gastric. On the 7th , 14th and 21st days of treatment were compared with healthy plumbing. By take of 50 mg/kg of this preparation there had been increased overall bioelectrical activity of the stomach by 1.78-1.88 (P<0.05), the pulse frequency of the stomach by 1.04-1.29 (P<0.05), and the mean amplitude of the stomach by 1.26-1.44 (P<0.05) is shown that it has a gastro protector activity. DOI: http://dx.doi.org/10.5564/mjas.v11i2.208 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.13-16